Phytoplankton dynamics in relation to Red tide appearance in Qarun Lake, Egypt - Ezzat A. Ibrahim; Shymaa S. Zaher; Wael M. Ibrahim; Yassmeen A. Mosad (Egyptian Journal of Aquatic Research, 2021)
Qarun Lake is a unique saline basin. Its phytoplankton species abundance and dynamics in relation to the Red Tide phenomenon is the focus of this study. Samples were collected from May 2015 to April 2016 in twelve successive cruises. Phytoplankton productivity attained the highest level on July with the bloom of Dinophyceae, while showing negative correlation with water transparency (r = −0.72) and positive correlation with DO (r = 0.84). The causative species was Gymnodinium lantzschii. Another incident of Dinophyceae bloom was observed in March when chlorophyll a recorded 158.4 mgm−3, chl. b was (92.7 mgm−3 and chl. c was 160 mgm−3. The causative species were Prorocentrum aporum and Prorocentrum micans and the lake’s water turned to red color; the “Red Tide phenomenon”. Chlorella vulgaris bloom was recorded for the first time in the lake on August at site (4) with green water discoloration. The water temperature of the lake was one of the main phytoplankton bloom’s drivers as the dominant species grew and flourished within a narrow range of temperature (30.4–34.9 °C). The results showed that there were strong correlations between carbonate, bicarbonate, DO and nutrients indicating that the dinoflagellate bloom was due to the high eutrophication of the lake. Finally, the Red tide phenomenon may influence the lake fisheries causing significant economic loss.